The colonel's daughter - King, Charles, 1844-1933; Harmer, Alexander Francis, 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2025)
"The colonel''s daughter: or, Winning his spurs" by Charles King is a novel written in the late 19th century. Set on the Arizona frontier, it entwines military life and romance, centering on adjutant John Truscott, impulsive young lieutenant Arthur Glenham, and Grace Pelham, the colonel$1 (Bs daughter, amid garrison routines, social maneuvering, and rising Apache unrest. Expect brisk soldierly realism, sharp drawing-room tensions, and a quietly forming love triangle pressed by the threat of war. The opening of the novel paints Camp Sandy in blistering heat, introducing the disciplined, reserved Truscott; the warm-hearted, wealthy Glenham; and the talkative, factional garrison community awaiting the arrival of Colonel Pelham$1 (Bs wife and the much-admired Grace. Gossip swirls about Grace and Glenham, while Truscott$1 (Bs integrity, past clashes with meddling superiors, and quiet generosity are established when he sacrifices his own trip so Glenham can attend the Prescott festivities. At the Prescott ball, Grace$1 (Bs beauty captivates all, her mother manages access, and local rivalries flare, even as Truscott is delayed by urgent duty. During the night, alarms spread that the Tonto Apaches have left the reservation; bugles sound, officers are summoned, and Glenham, having just been gently refused by Grace, is swept toward field service. In parallel, Truscott rides alone through the mountains, discovers the murdered mail-carrier and a ranch in flames, and pushes on, signaling the outbreak that will drive the story from ballroom to battlefield. (This is an automatically generated summary.)s
Release date is 2025-09-04
Brian Coe, Thiers Halliwell (cover image restoration), Quentin Campbell and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Soldiers -- Fiction; Man-woman relationships -- Fiction; United States. Army -- Officers -- Fiction; Arizona -- History -- To 1912 -- Fiction